Garment Quality of Biodegrable "Lydia Zois" as an Application of Neo-Eco and Sustainable Fashion - Putri, Syifa Nurhaliza; Wahyuningsih, Sri Endah (Journal of Creativity Student, 2026)
The global fashion industry currently faces serious challenges due to massive textile waste and greenwashing practices. In response, “Lydia Zois” clothing emerges with a Neo-Eco concept that integrates biodegradable materials and inspiration from bamboo weaving architecture. This study aims to analyze the quality of Lydia Zois clothing based on the evaluation of expert and trained panelists across six indicators: design, fit, aesthetics, sewing techniques, garment performance, and special product features. The research method employed is a quantitative descriptive approach. Data were collected through feasibility tests involving 5 expert panelists and 20 trained panelist using an assessment sheet with two clear response options: ‘Yes’ and ‘No’. the data were analyzed using percentage descriptive analysis. The results indicated that the overall average quality of Lydia Zois clothing is 95 % categorized as “Highly Suitable.” The highest scores reached 97% in the indicators of fit, garment performance, and special product features. The study concludes that Lydia Zois successfully integrates modern aesthetics with sustainability principles through innovative bamboo weaving details. However, aspects such as pressing techniques and lining efficiency remain key evaluation points for enhancing the quality of ready to wear garments in the future.